Puppet 4.10 beginner's guide : go from newbie to pro with Puppet 4.10 - Arundel, John (Packt Publishing, 2017)
Puppet is great for developers, system administrators, IT professionals, and anyone laying the foundation for DevOps practices ? this comprehensive guide will get you up to speed, all the way from installation to automation to the latest features of Puppet 4.10. About This Book Develop skills to run Puppet 4.10 on single or multiple servers without hiccups Use Puppet to spin up and manage cloud resources such as Amazon EC2 instances Take full advantage of the powerful new features of Puppet 4.10, including loops, data types, structured facts, R10K module management, control repos, and EPP templates Who This Book Is For Puppet Beginner's Guide, Second Edition is designed for those who are new to Puppet, including system administrators and developers who are looking to manage computer server systems for configuration management. No prior programming or system administration experience is assumed. What You Will Learn Covers the latest Puppet 4.10 release Install and set up Puppet and discover the latest and most advanced features Configure, build, and run containers in production using Puppet's industry-leading Docker support Deploy configuration files and templates at super-fast speeds and manage user accounts and access control Automate your IT infrastructure Use the latest features in Puppet 4 onward and its official modules Manage clouds, containers, and orchestration Get to know the best practices to make Puppet more reliable and increase its performance In Detail Puppet 4.10 Beginner's Guide, Second Edition, gets you up and running with the very latest features of Puppet 4.10, including Docker containers, Hiera data, and Amazon AWS cloud orchestration. Go from beginner to confident Puppet user with a series of clear, practical examples to help you manage every aspect of your server setup. Whether you're a developer, a system administrator, or you are simply curious about Puppet, you'll learn Puppet skills that you can put into practice right away. With practical steps giving you the key concepts you need, this book teaches you how to install packages and config files, create users, set up scheduled jobs, provision cloud instances, build containers, and so much more. Every example in this book deals with something real and practical that you're likely to need in your work, and you'll see the complete Puppet code that makes it happen, along with step-by-step instructions for what to type and what output you'll see. All the examples are availa...